PERAN GURU SEKOLAH DASAR DALAM PEMBELAJARAN DI ERA TEKNOLOGI DIGITAL - Denizulaiha, Denizulaiha (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The development of information technology has promised great potential in changing the way one learns, to obtain information, adjust information and so on. Technology also provides opportunities for educators to develop learning techniques to produce maximum results. Similarly for elementary school teachers, with technology it is expected they are easier to determine with what and how students can absorb information appropriately and efficiently. The results of the discussion: (1) in the global digital community should be carried out at least three lessons, namely Learning which emphasizes on: (a) search and discovery construction; (b) creativity and initiative; (c) interaction and cooperation; (2) the role of teachers in learning the digital age is the teacher as: (a) learning resources; (b) the facilitator; (c) managers; (d) the demonstrator; (e) mentors; (f) motivators; (g) evaluators; (3) the challenge of the digital age teacher; 4) coping strategy challenge: teacher becomes the bridge of revolution.